Application of Artificial Intelligence Technology in Computer Network Security Communication. (21st July 2022) - Li, Fulin
Abstract : In order to cope with the frequent challenges of network security issues, a method of applying artificial intelligence technology to computer network security communication is proposed. First, within the framework of computer network communication, an intelligent protocol reverse analysis method is proposed. By converting the protocol into an image and establishing a convolutional neural network model, artificial intelligence technology is used to map the data to the protocol result. Finally, use the model to test the test data to adjust the model parameters and optimize the model as much as possible. The experimental results show that compared with the test model, the results obtained after training with the deep convolutional neural network model in this paper have increased the accuracy by 2.4%, reduced the loss by 38.2%, and reduced the running time by 42 times. The correctness and superiority of the algorithm and model are verified.